A gelatin hydrogel to study endometrial angiogenesis and trophoblast invasion. Issue 5 (6th October 2019) - Zambuto, Samantha G.; Clancy, Kathryn B. H.; Harley, Brendan A. C.
Abstract : The endometrium is the lining of the uterus and site of blastocyst implantation. Each menstrual cycle, the endometrium cycles through rapid phases of growth, remodelling and breakdown. Significant vascular remodelling is also driven by trophoblast cells that form the outer layer of the blastocyst. Trophoblast invasion and remodelling enhance blood flow to the embryo ahead of placentation. Understanding the mechanisms of endometrial vascular remodelling and trophoblast invasion would provide key insights into endometrial physiology and cellular interactions critical for establishment of pregnancy. The objective of this study was to develop a tissue engineering platform to investigate the processes of endometrial angiogenesis and trophoblast invasion in a three-dimensional environment. We report adaptation of a methacrylamide-functionalized gelatin hydrogel that presents matrix stiffness in the range of the native tissue, supports the formation of endometrial endothelial cell networks with human umbilical vein endothelial cells and human endometrial stromal cells as an artificial endometrial perivascular niche and the culture of an endometrial epithelial cell layer, enables culture of a hormone-responsive stromal compartment and provides the capacity to monitor the kinetics of trophoblast invasion. With these studies, we provide a series of techniques that will instruct researchers in the development of endometrial models of increasing complexity.